ANALISA KESTABILAN MODEL MATEMATIKA PENYAKIT PNEUMONIA DENGAN CARRIERS - Hanik Rahmawati (Jurnal Matematika, 2015)
ABSTRACT. Pneumonia disease is lung infammation disease caused by microorganism such as Streptococcus pneumoniae bactery. This final project presented a mathematical model that describe dinamic pneumonia disease population in children under five years. The model used SICR are susceptible, infected, carriers, and recovered. Analysis to the model is conducted to decide whether pneumonia will spread within population with reproduction number. Using Routh-Hurwitz criterion we obtained free disease equilibrium and endemic equilibrium. From stability analysis of simulation result it is known that the disease free eqilibrium unstable while the endemic equilibrium stable local asimtotic with .